Formula for multiplication of solutions of the Cortevegs—de Fries equations - Fushchich , V. I.; Tychinin , V. A.; Serov , N. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A formula of the multiplication of solutions of the Kortweg-deVries equation is proposed. With the help of the indicated formula, sets are constructed of solutions of the indicated equation. The Riccati equations are solved, which appear in the multiplication process.